Influence of Hypnobirthing on Labor Pain Intensity in Sidamulya, Cirebon, West Java - Elok Paikoh; Nunung Nurjanah; Erni Ratna Suminar; Aulia Ridla Fauzi; Neli Sunarni (Yayasan Inspirasi El Burhani, 2023)
Introductions: One of the reasons for the painful labor experience is the psychological factor, such as fear and excessive anxiety, which can intensify the perception of pain and potentially lead to complications during childbirth. To address this issue, Hypnobirthing Therapy is often employed as a method to help manage and reduce pain and anxiety during labor. Objectives: To assess the impact of Hypnobirthing Therapy on pain intensity during childbirth at TPMB Regional Health Center Sidamulya in Cirebon Regency in the year 2023. Methods: This study employs a pre-experimental design with a one-group pretest-posttest design. The research sample consists of 30 women who are giving birth during phase I of active labor, selected using a purposive sampling technique. The intervention involves providing mothers with a 10-minute guided session using a cellphone during labor. Bivariate analysis will be conducted using a paired T-test. Results: Univariate results show that, before receiving Hypnobirthing Therapy, the majority of mothers experienced severe pain intensity, accounting for 27 respondents (90%), while the remaining 14 individuals (46.7%) reported experiencing current pain intensity. The Wilcoxon test yielded a p-value of 0.000, which is less than 0.05, indicating a statistically significant difference. Conslussions: Hypnobirthing Therapy is effective in reducing the intensity of pain during childbirth. In this context, midwives are expected to administer labor care by offering Hypnobirthing Therapy to mothers. This helps mothers relax and feel comfortable, ultimately preparing them for a normal childbirth experience.